A Conceptual Paper Approach on the Effects of Psychological Contract Breach Among University Employees in Pakistan: Moderating Role of Perceived Organisational Support - Rana Humayun, Ihsan; Norizan, Jaafar; Kartinah, Ayyup; Bilyaminu, Usman (HRMARS, 2020)
Psychological contract breach (PCB), which is an unwritten expectations-based contract between an employee and an employer, leads to negative attitudes and behaviours. PCB may be avoided by a number of ways. This paper argues that perceived organisational support (POS) may be used to mitigate the negative effects of PCB towards turnover intention (TI), job dissatisfaction (JS) and counterproductive work behaviours (CWB). This study proposes that PCB may be investigated using different samples so that results may be compared within and outside Pakistan. This paper is also presented as a proposed conceptual framework for future research based on theoretical triangulation from previous seminal studies in the international, the Asian and the Pakistani context. Keywords:Psychological Contract Breach, Job Satisfaction, Turnover Intention, Counterproductive Work Behaviour, Perceived Organisational Support.